Localized co-delivery of CNTF and FK506 using a thermosensitive hydrogel for retina ganglion cells protection after traumatic optic nerve injury - Dongmei Wang; Mengmeng Luo; Baoshan Huang; Wa Gao; Yan Jiang; Qing Li; Kaihui Nan; Sen Lin (Drug Delivery, 2020)
Following the traumatic axonal injury in the optic nerve, the failure of retrograde axonal transport to continuously supply neurotrophins from the brain to retina results in deprivation of neurotrophins in retinal ganglion cells (RGCs), which in turn can modulate the fate of RGCs toward apoptosis and thereby impede axon regeneration. In this study, a ciliary neurotrophic factor (CNTF) loaded thermo-sensitive hydrogel was designed and developed as a localized drug depot to restore neurotrophins supply following axon injury. Besides, following traumatic axon injury, overactive immune responses cause neurotoxicity and induce scar formation which together constitutes the major hindrances for axon regeneration. Thus, the FK506, a hydrophobic macrolide immunosuppressant, was co-loaded into the hydrogel after encapsulating it into a polymeric micelle. The materials can undergo sol-to-gel transition within minutes under a physiological pH of 37 °C. The release of drugs from the hydrogel exhibited a sustainable profile in vitro. The optic nerve was exposed by surgical procedure and the animal model was prepared by crushing the nerve with a reverse clamp. For the localized delivery to the optic nerve, a pre-hydrogel liquid containing chitosan, FK506 (in micelle), CNTF, and the gelling agent was directly smeared on the injured site, which gelled under physiological condition. This co-delivery system exhibited in vivo RGCs protective effect against the adverse effects caused by traumatic optic nerve injury, indicating the potential of this drug delivery system for effective optic nerve repair and this strategy may provide promising platforms for localized drug delivery in various other therapies.